The Adaptive Control in the Plastic Injection Molding - Hartono, Mohammad; Pratikto, Pratikto; Budi, Purnomo; Sugiono, Sugiono (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.371, 2017)
Progress in the manufacturing industry is growing very rapidly. But it had an impact on environmental pollution. One of them is contamination caused by plastic. Plastic contamination is the most severe pollution because plastic elements can not be broken down by decomposer bacteria. This paper discusses the need for an action to minimize pollution caused by plastics. The principle is to use as much as possible recycled plastic to be re-processed into useful plastic products and minimize plastic waste products. With increasingly sophisticated technology in the field of control, adaptive control is a real-time control method for monitoring plastic raw materials to be processed and can instantaneously adjust to the plastic mold control panel that minimizes product defects. Therefore, the use of adaptive controls in the plastic molding process can minimize waste from plastics that are part of the green technology.